Controlling computers and electronics waste: toward solving environmental problems - Hameed, Shihab A. (2012)
Environment problem becomes an essential issue associated modern life in this century. Advancement in electronic production and cost reduction in the last few decades leads to rapid growing of computers and electronic productions (e-devices). This was associated with flood of advertisements which affect customer’s decision on buying new products regardless of their real needs. Although e-devices improved human life but it created a serious environmental problem called e-waste. Millions of tons of e-waste generated worldwide yearly, which is more toxic and harmful than normal household garbage. E-waste contains toxic heavy metals including arsenic, antimony, lead, mercury, nickel and zinc. Increasing consumption of e-devices in developing countries and transferring e-waste from developed to developing countries make the problem worst. So we need an innovative and creative engineers and effective recycling system to produce eco-friendly products that are easier to recycle and handle in their end-of-life. Several developing countries in Asia, Africa and Latin America still suffer from lack of advance recycling and disposal treatment experience. Workers in recycling are exposed to hazardous chemicals and material when braking e-products and extracting its valuable contents besides the polluting of water, air and soil. This paper studying the e-waste status and proposes a framework for guidance solution to control and eliminate e-waste, protecting workers and environment in developing world as step toward green environment.